Дослідження несиметричного режиму на роботу динамічного індуктивного навантаження - Попова, Ірина Олексіївна; Квітка, Сергій Олексійович; Вовк, Олександр Юрійович; Popova, Iryna; Kvitka, Serhii; Vovk, Oleksandr (Запоріжжя : 2023, 2023)
UA: В роботі проаналізовано причини виникнення несиметрії напруг у електричній мережі напругою до 1000 В. Запропоновано методику розрахунку фазних струмів при несиметрії напруг мережі при одночасному включенні однофазних і симетричних трифазних споживачів динамічного індукційного характеру (асинхронних двигунів з короткозамкненим ротором). Дослідження передбачає еквівалентне перетворення, при якому несиметричне трифазне навантаження замінено на еквівалентне симетричне навантаження; симетрична лінія електропередачі з однаковими опорами замінена несиметричною лінією електропередачі з різними опорами. Режим мережі описано системою рівнянь згідно методу симетричних складових, законів Кірхгофа і комплексних чисел. Наведені рівняння розрахунку фазних струмів динамічного індуктивного навантаження в залежності від напруг і опорів прямої і зворотної послідовностей і математичні рівняння розрахунку опорів прямої і зворотної послідовностей динамічного індуктивного навантаження в залежності від частоти обертання (ковзання). Приведені рівняння ковзання динамічного навантаження в залежності від коефіцієнта несиметрії напруги зворотної послідовності, моментів прямої і зворотної послідовності та моменту опору робочої машини для різних коефіцієнтів, що характеризують механічну характеристику робочої машини. Приведена методика аналізу дозволяє розрахувати фазні струми динамічного індуктивного навантаження в несиметричному режимі. EN: The paper analyzes the causes of voltage asymmetry in the distribution network with a voltage of up to 1000 V. a method for assessing the state of asymmetry of a four-wire distribution network with simultaneous inclusion of single-phase and symmetrical three-phase consumers of a dynamic induction nature (asynchronous motors with a short-circuited rotor) is proposed. The study involves an equivalent transformation in which an unbalanced three-phase load is replaced by an equivalent symmetrical load; a symmetrical power line with the same resistances is replaced by an unbalanced power line with different resistances. The calculation of the coefficients of the ratios of Phase voltages between the neutral of the power supply to the terminals of a dynamic inductive load is provided for calculating the resistances of an unbalanced equivalent power line depending on the voltage asymmetry in the distribution network. The network mode is described by a system of equations according to the symmetric component method, Kirchhoff's laws, and complex numbers. Equations for calculating the phase currents of dynamic inductive load depending on the voltages and resistances of the forward and reverse sequences and mathematical equations for calculating the resistances of the forward and reverse sequences of dynamic inductive load depending on the speed of rotation (sliding) based on the parameters of a simplified asynchronous motor replacement scheme are given. Mathematical equations of the dependence of the sliding of a dynamic load (asynchronous motor) on the coefficient of asymmetry of the reverse sequence voltage, moments of the forward and reverse sequence depending on the asymmetry of the mains voltages and the moment of resistance of the working machine for various coefficients that characterize the mechanical characteristic of the working machine are given. The inverse sequence coefficient is calculated for linear network voltage complexes. The presented method makes it possible to calculate the phase currents and voltages of a dynamic inductive load, taking into account the voltage asymmetry coefficient of the reverse sequence, the load coefficient of the working machine.
Investigation of an unbalanced mode in a distribution network with a dynamic inductive load
Keywords: симетричні складові; фазний струм; динамічне індуктивне навантаження; опір; коефіцієнт завантаження; коефіцієнт несиметрії напруги зворотної послідовності; symmetric components; phase current; dynamic inductive load; resistance; reverse sequence voltage asymmetry coefficient; load factor